ASTRAELENIA SAOMAMEDENSIS N. SP. - A NEW GIGANTIC RHYNCHONELLID SPECIES AND ITS PALAEOBIOGEOGRAPHICAL IMPLICATIONS FOR THE PORTALEGRE SYNCLINE (CENTRAL PORTUGAL) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
A new species of Astraelenia is described from ?Siegenian to Emsian strata of the Portalegre Syncline (Central Portugal). Astraelenia saomamedensis n. sp. differs in a smaller number of costae, a rather inconspicuous fold and sulcus, and larger and elongate shells from other species of Astraelenia. Astraelenia occurs today in northern Africa, Central and Western Europe; the new species shows Gondwanan origin according to faunal elements found in the stratigraphic vicinity. The migration of Astraelenia is described considering Lower Devonian regional transgression and regression events. The new species is found in monospecific clusters and an attempt for understanding its palaeoecology is presented.
Keywords: Astraelenia; Rhynchonellida; Brachiopoda; Stratigraphy; Palaeobiogeology; Palaeoecology; Lower Devonian; Portugal